Modeling of systems - Gamayun, I. P.; Cherednichenko, O. Yu. (Fakt, 2015)
The handbook contains the fundamentals of modeling of complex systems. The classification of mathematical models is represented and the methods of their construction are given. The analytical modeling of the basic types of processes in the complex systems is considered. The principles of simulation, statistical and business processes modeling are described. The handbook is oriented on students of higher education establishments that obtain a degree in directions of “Software engineering” and “Computer science” as well as on lecturers and specialists in the domain of computer modeling.
Keywords: mathematical modeling; analytical modeling; statistical modeling; simulation modeling; business-processes modeling